Faktor Dominan Yang Mempengaruhi Pertumbuhan Aset Pada Lembaga Keuangan Mikro Syariah Di Jawa Barat - Muhammad Ali Fikri; Trisiladi Supriyanto; Qurroh Ayuniyyah (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine the dominant factors affecting the growth of assets of Islamic Microfinance Institutions in West Java. Besides this research is aimed at finding out how much influence the Third-Party Funds (DPK), Financing Received (PYD), Capital, Non-Performing Finance (NPF) and Profit (SHU) on the Growth of Assets of Islamic Microfinance Institutions in West Java. This research was conducted at Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) in West Java with data collection techniques based on published data that have been validated in RAT and analyzed using descriptive analysis methods with a quantitative approach. The variables examined in this study are the variables of DPK, PYD, capital, NPF and Sisa Hasil Usaha (SHU) as independent variables and Asset as the dependent variable. As for testing the hypothesis, multiple correlation regression analysis was used with significance level of 0.05 with the help of the SPSS Version 26 and Microsoft Excel 2019 programs. The results of data processing and analysis in this study can be concluded that the dominant factor affecting the growth of LKMS assets that 1) TPF has a significant effect on assets 2) PYD has a significant effect on assets. 3) Capital has a significant effect on assets 4) NPF does not have a significant effect on assets 5) SHU does not have a significant effect on assets. However, DPK, PYD, Capital, NPF and SHU altogether have an effect on Assets.